RETROSPECTIVE EVALUATION OF DIFFERENT FODDER REGIMENS AND CLIMATE ON PREGNANCY RATE IN JERSEY CROSSBRED COWS OF SUBTEMPERATE REGION - SOOD, PANKAJ; THAKUR, Y P; SINGH, MADHUMEET; RANI, DESY; BURMAN, POORBI; RUTHWAL, ANOOP; SHARMA, RAJESH; KUMAR, NAVEEN (The Indian Journal of Animal Reproduction, 2023)
The present study compared separately a retrospective assessment of association of 17 different fodderregimens and three different classes of temperature - humidity index (THI) with per cent pregnancy rates(PRs), following 3,264 artificial inseminations (year 1998 to 2008) in Jersey crossbred cows. The similar foddercombinations and THI were separately clubbed on monthly basis for their association with PR. The greenfodder(s) offered to the cows comprised of maize, oats and other green fodders (OGF) namely Seteria, Napier,Kikuyu, Berseem and Sorghum. In addition, silage and wheat straw were also supplemented. The two highestPRs of 41.4% and 40.9% were associated, respectively, with feeding of fodder combinations having 36.3%and 35.4% silage of the total fodder, respectively. Considered together, feeding different fodder combinationsof greens having 38.8% to 95.1 % maize resulted in a PR of 32.8%, which was less (P=0.10) than 37.5% asrecorded with other fodder combinations not having maize. The PR at different THI categories of 50-60, 61-70and 71-75, respectively, were similar and ranged from 35.0 to 38.0%. In conclusion, pregnancy rates werehigher in cows provided silage with green fodder than the others given maize fodder dominated diets. Thelatter needs to be investigated for the associated mechanism(s) reducing pregnancy rates.
Keywords: Cattle; Fodder; Pregnancy; Temperature-humidity index